Correlates of the use of electronic devices to vape cannabis in a cohort of young Swiss male reporting current cannabis use. (9th November 2020) - Fuster, Daniel; Studer, Joseph; Gmel, Gerhard; Bertholet, Nicolas
Abstract: Background: Information about correlates of cannabis vaping in Europe is scarce. Methods: In a cohort of 1613 Swiss young males currently using cannabis, we used logistic regression, adjusting for age, linguistic region and education to assess the association between sensation seeking, substance use and sociodemographic variables with cannabis vaping. Results: Mean age was 25.38 years, 60.4% had post-secondary education and 57.3% lived in French-speaking cantons; 26.3% met criteria for nicotine dependence, 16.0% met criteria for alcohol use disorder and 34.9% used illicit drugs other than cannabis; 27.4% used cannabis at least twice a week and 27.8% met criteria for cannabis use disorder (CUD). Ninety-four participants (5.8%) reported cannabis vaping (of them 87.4% reported infrequent cannabis vaping). In the adjusted analysis, using joints with no tobacco {adjusted odds ratio (aOR) [95% confidence interval (CI)] = 1.45 (1.02–1.76)}, water pipe with [aOR (95% CI) = 1.70 (1.29–2.24)] and without tobacco [aOR (95% CI) = 2.15 (1.60–2.87)], cannabis mixed with food [aOR (95% CI) = 1.61 (1.29–2.02)], using cannabis >2 times a week [aOR (95% CI) = 3.73 (2.40–5.81)], meeting criteria for CUD [aOR (95% CI) = 4.19 (2.70–6.50)], using illicit drugs other than cannabis [aOR (95% CI) = 1.88 (1.23–2.87)], weekly number of alcohol drinks [aOR (95% CI) = 1.01 (1.00–1.03)] and living in the German-speaking area of Switzerland [aOR (95% CI) = 2.70 (1.71–4.25)] were associated with higher odds of cannabis vaping; post-secondary schooling [aOR (95% CI) = 0.37 (0.16–0.86)] and vocational training [aOR (95% CI) = 0.41 (0.17–0.99)] (as opposed to primary schooling) were associated with lower odds of cannabis vaping. Conclusion: Cannabis vaping might be a marker of riskier behaviours among cannabis users.